2021
DOI: 10.1029/2021jd034630
|View full text |Cite
|
Sign up to set email alerts
|

Stable Mercury Isotopes Revealing Photochemical Processes in the Marine Boundary Layer

Abstract: Atmospheric mercury (Hg) can be operationally defined into three types: gaseous elemental Hg (GEM), gaseous oxidized Hg (GOM), and particle-bound Hg (PBM). GEM is the most abundant Hg species in the global atmosphere (approximately 90%) and is well mixed due to its prolonged lifetime (0.5-1 year) and stable chemical properties. As GOM and PBM are more soluble in water than GEM and have a shorter lifetime (days to weeks), they are the predominant Hg species deposited to ecosystems through wet and dry deposition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 72 publications
1
21
1
Order By: Relevance
“…City-specific mean δ 202 Hg, Δ 199 Hg, and Δ 200 Hg values of PBM during the study period ranged from −2.00 to −0.78, −0.04 to 0.47, and 0.02 to 0.06‰ ( n = 10), respectively, while the overall mean from all the 10 cities were −1.16, 0.22, and 0.05‰, respectively (Figure and Table S3). PBM isotopic compositions observed in the present study align well with the pool of global PBM data, which are characterized by significantly negative δ 202 Hg (mean = −1.64 to −0.69‰), slightly negative to significantly positive Δ 199 Hg (mean = −0.21 to 0.83‰), and positive Δ 200 Hg (mean: 0.01 to 0.14‰) signatures (Table S3), ,, with the exception of the observations in polar regions (mean δ 202 Hg = 0.03 to 1.05‰, mean Δ 199 Hg = −0.38 to −0.28‰, mean Δ 200 Hg = −0.01 to 0.00‰, n = 2) (Table S3). , By comparison, PBM at urban sites worldwide showed relatively lower Δ 199 Hg and Δ 200 Hg values as compared to observations at Chinese rural sites, in marine air, and at a coastal site in the United States (Figure ).…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…City-specific mean δ 202 Hg, Δ 199 Hg, and Δ 200 Hg values of PBM during the study period ranged from −2.00 to −0.78, −0.04 to 0.47, and 0.02 to 0.06‰ ( n = 10), respectively, while the overall mean from all the 10 cities were −1.16, 0.22, and 0.05‰, respectively (Figure and Table S3). PBM isotopic compositions observed in the present study align well with the pool of global PBM data, which are characterized by significantly negative δ 202 Hg (mean = −1.64 to −0.69‰), slightly negative to significantly positive Δ 199 Hg (mean = −0.21 to 0.83‰), and positive Δ 200 Hg (mean: 0.01 to 0.14‰) signatures (Table S3), ,, with the exception of the observations in polar regions (mean δ 202 Hg = 0.03 to 1.05‰, mean Δ 199 Hg = −0.38 to −0.28‰, mean Δ 200 Hg = −0.01 to 0.00‰, n = 2) (Table S3). , By comparison, PBM at urban sites worldwide showed relatively lower Δ 199 Hg and Δ 200 Hg values as compared to observations at Chinese rural sites, in marine air, and at a coastal site in the United States (Figure ).…”
Section: Resultssupporting
confidence: 88%
“…Mean (±1sd) of δ 202 Hg vs Δ 199 Hg (A) and δ 202 Hg vs Δ 200 Hg (B) for PBM collected in the 10 megacities in this study. Observations of δ 202 Hg, Δ 199 Hg, and Δ 200 Hg for PBM in rural areas of China, oceans, urban areas of South Asia, , and USA, as well as Hg(0) (GEM) in urban and rural areas of China ,, were also compiled from previous studies. Error bars are 1sd of the mean values.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Most physical and chemical processes lead to MDF, but odd-MIF is mainly produced by photochemical reactions (e.g. photoreduction of aqueous Hg­(II), photodemethylation of methylmercury). Even-MIF is mainly observed in atmospheric samples, and its mechanism may be attributed to atmospheric redox processes. Previous studies have reported Hg isotopes of PBM in different regions (e.g., urban, rural, and coastal areas) , and seasonal even diurnal variation of odd-MIF ,, and indicate that the isotopic compositions of PBM emitted from primary sources would be modified during atmospheric transformation or transportation. However, the mechanism that drives Hg isotope variations of PBM is still poorly understood, especially during the transformations of PBM in severe haze events.…”
Section: Introductionmentioning
confidence: 99%